1998
DOI: 10.1038/bjc.1998.576
|View full text |Cite
|
Sign up to set email alerts
|

Absence of 185delAG mutation of the BRCA1 gene and 6174delT mutation of the BRCA2 gene in Ashkenazi Jewish men with prostate cancer

Abstract: Summary Epidemiological studies have demonstrated a clustering of breast and prostate cancers in some families. Moreover, there is an increase in the number of cases of prostate cancer in families with inherited mutations of the breast cancer susceptibility gene BRCA 1. We assessed the role of BRCA1 and BRCA2 in prostate cancer. We tested for the BRCAl 185delAG frameshift mutation, found in 0.9% of Ashkenazi Jews, and the BRCA2 6174delT mutation, found in 1% of Ashkenazi Jews, in Ashkenazi Jewish men with pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…Of note, had we excluded patients with personal or familial history of BC from the patient cohort as well as from the control group analysed, the lack of association between these mutations and CRC would be even more striking. Taken together with the recent publications showing these specific mutations do not increase the risk for prostate cancer in this ethnic group (Lehrer et al, 1998;Hubert et al, 1999;Vazina et al, 2000), we can conclude that the predominant Ashkenazi Jewish BRCA1 and BRCA2 mutations do not contribute to the pathogenesis of CRC. Thus, it seems that the two major indications for performing BRCA1/2 genetic testing in men are the personal risk for developing BC (Struewing et al, 1999) and the risk of transmitting the mutated alleles to their daughters.…”
Section: Discussionsupporting
confidence: 78%
“…Of note, had we excluded patients with personal or familial history of BC from the patient cohort as well as from the control group analysed, the lack of association between these mutations and CRC would be even more striking. Taken together with the recent publications showing these specific mutations do not increase the risk for prostate cancer in this ethnic group (Lehrer et al, 1998;Hubert et al, 1999;Vazina et al, 2000), we can conclude that the predominant Ashkenazi Jewish BRCA1 and BRCA2 mutations do not contribute to the pathogenesis of CRC. Thus, it seems that the two major indications for performing BRCA1/2 genetic testing in men are the personal risk for developing BC (Struewing et al, 1999) and the risk of transmitting the mutated alleles to their daughters.…”
Section: Discussionsupporting
confidence: 78%
“…It demonstrated that BRCA2 mutation carriers have a relative risk (RR) of PRCA of 4.65 rising to 7.33 below the age of 65 years and BRCA1 mutation carriers have an RR of PRCA of 1.82 under the age of 65 years (BCLC, 1999; Thompson et al, 2002). Similar data have been recorded in the AJ population (Struewing et al, 1997;Warner et al, 1999;Giusti et al, 2003), although smaller clinical studies have generally not demonstrated an increased frequency of founder BRCA1/2 mutations among Jewish men with PRCA (Lehrer et al, 1998;Hubert et al, 1999;Nastiuk et al, 1999;Vazina et al, 2000). In the current data set, six men were identified from a previous study conducted at The Institute of Cancer Research, as described in the Materials and Methods section.…”
Section: Discussionmentioning
confidence: 71%
“…An additional study failed to identify an increased risk of breast cancer in relatives of patients with prostate cancer (Issacs et al, 1995). One BRCA1 germline mutation carrier with CaP and familial cancer was reported among 24 Japanese CaP patients, no 185delAG or 6174delT mutation carriers were detected among 60 Ashkenazi CaP patients (Lehrer et al, 1998), and one 6174delT BRCA2 mutation carrier was found among 47 Jewish Ashkenazi individuals from 18 families with familial CaP (Wilkens et al, 1999). Recently, three mutation carriers (two with the 185delAG and one harbouring 6174delT) were identified among 87 unselected prostate cancer patients from Israel (Hubert et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the lifetime risk for developing CaP in Ashkenazi BRCA1 or BRCA2 mutation carriers was estimated at 16% (Struewing et al, 1997). However, direct mutational analysis of 60 unselected Jewish Ashkenazi CaP patients did not reveal any BRCA1 or BRCA2 mutation carrier (Lehrer et al, 1998).…”
mentioning
confidence: 99%